(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2021)
The research to determine the marketing development strategy in an effort to increase sales of processed nutmeg meat products carried out in Small and Medium Industries in Ternate City. with the consideration that these IKM have developed in creating product diversification, varied selling prices and forms of service to consumers, so that they have potential. The analytical method used is the Analytical Hierarchy Process (AHP) which consists of three levels, namely goals, criteria, and alternatives to identify and classify marketing mix strategies in marketing processed nutmeg meat products by determining criteria and selecting alternative strategies based on similar characteristics in decision making. The results showed that the goal of the marketing mix selection strategy in an effort to increase sales of processed nutmeg meat products as a whole was the affordable price criterion with a weight of 0.245, and the alternative choice of the price strategy with a weight of 0.403 indicated that price was the main determining factor in purchasing, so that the Ternate City IKM actors in determining the selling price prefer to provide affordable prices, because low price products can provide an image and believe that the need for products will always continue in the long term.